APPLICATION OF CALCULATION OF VALUE OF GOODS IN PERUM MORTGAGE APPRAISER USING MICROSOFT VISUAL BASIC 6.0 - Lidya Meilawati; Susi Wagiyati P, SKom, MMSI (Jurnal Sistem Informasi, 2004)
The use of computers in PERUM mortgaging has become a vital need, in the present writer has not seen that PERUM mortgaging optimize existing computer usage. In other words the processes being run over is still manual.To the authors try to make a design program in order to simplify the process of calculating the value of goods on state owned mortgage appraiser so that existing data can be processed faster and more accurate by using the application programming language Microsoft Visual Basic 6.0.